2018
DOI: 10.1016/j.ihj.2017.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Real-time three-dimensional echocardiographic left heart parameters in healthy indian adults

Abstract: Objective Cardiac chamber dimensions are race and anthropometry dependent. We determined the age and gender specific 3-Dimensional echocardiographic (3DE) reference values for dimensions and function of left ventricle (LV) and left atrium (LA) in normal Indian adults. Methods This single center prospective study enrolled 133 adult Indians free of heart disease and/or hypertensions, subjecting them to 3DE measurements of left atrial (LA) & left ventricular (LV) volumes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The preliminary reports from the WASE study support these results [33,34]. The upper limit of normal (ULN) for 3D LV volumes were found to be lower for Japanese and Indian Asians than for Europeans [26,[29][30][31]. However, for these studies, 3D LV volume datasets were acquired with apparatus from different vendors, and LV volumes were analyzed using a variety of software.…”
Section: Sizementioning
confidence: 85%
See 1 more Smart Citation
“…The preliminary reports from the WASE study support these results [33,34]. The upper limit of normal (ULN) for 3D LV volumes were found to be lower for Japanese and Indian Asians than for Europeans [26,[29][30][31]. However, for these studies, 3D LV volume datasets were acquired with apparatus from different vendors, and LV volumes were analyzed using a variety of software.…”
Section: Sizementioning
confidence: 85%
“…Recently, the WASE Normal Values study used a uniformed measurement protocol to examine in two core laboratories data for over 2000 normal subjects enrolled worldwide, and found only minor differences for LV size among races and countries, although the normal reference values recommended in the current guidelines need to be adjusted [15]. Regarding 3DE, the current guidelines recommend normal values for 3D LV volumes on the basis of three studies published a decade ago [24][25][26], although several studies have reported that normal reference values for LV volumes were different in a variety of countries and regions [27][28][29][30][31][32] (Table 1). According to most of these publications, 3D LV volumes were larger than 2D LV volumes, as well as larger for males than for females even after indexing to BSA, while they decreased with age for both genders.…”
Section: Sizementioning
confidence: 95%
“…AASV, Active atrial stroke volume; PASV, Passive atrial stroke volume; TASV, Total atrial stroke volume shape. 10,11 Normal 3D echocardiographic LA volumetric variables have been demonstrated in adults 12,13 and in elderly subjects. 13,14 These variables were also defined in children by 3D echocardiography using a commercial speckle-tracking package.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Normal 3D echocardiographic LA volumetric variables have been demonstrated in adults 12,13 and in elderly subjects. 13,14 These variables were also defined in children by 3D echocardiography using a commercial speckle-tracking package. 15 The 3DSTE technique takes one step forward: by using created virtual 3D cast, not only volumetric but also strain data can be measured at the same time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation